Association between Knowledge and Social Environment with Smoking Behavior Among University Students - Nida Amalia; Ghozali; Sri Sunarti; Kresna Febriyanto (Nusantara Science and Technology Proceedings, 2022)
It’s important to intervene with young people, especially regarding smoking, because if they start smoking they will be addicted and will continue to smoke until old age which can cause various health problems and even death. This study aims to describe and analyze the association between knowledge about cigarette smoking and social environment with smoking behavior among university students. This study used a cross-sectional design. Data was obtained by filling out online questionnaires. The study population was students of Universitas Muhammadiyah Kalimantan Timur with a sample of 311 respondents. Students with a smoking social environment were 267 people (85.9%) while students in a non-smoking social environment were 44 people (14.1%). Students with good knowledge were 91 people (29.3%) and students with no good knowledge 220 people (70.7%). Students who never smoked as many as 240 people (77.2%), former smokers 33 people (10.6%), and currently smokers 38 people (12.2%). The result of statistical analysis showed that there was no significant association between knowledge and social environment with smoking behavior. Students’ smoking behavior was not significantly related to their knowledge and their social environment. Several other factors may have more influence on students’ smoking behavior.